Retention of RN-to-BSN Students: An Integrative Review. - Gipson, Christine S.; Naldoza, Theresa; Ringhofer-Brown, Cindy; Stamer, Karie A.; Elliott, Brenda; Holmstrom, Jill M.; Rodgers, Esmeralda (Journal of Nursing Education, 2025)
Background: Student retention is problematic in higher education. RNs who desire to complete a Bachelor of Science in Nursing (RN-to-BSN) program face multiple barriers, and undergraduate nursing programs must be creative and comprehensive in their efforts to retain students and support their progression. Method: Toronto and Remmington's method guided this integrative review to identify strategies undergraduate nursing programs employ to retain RN-to-BSN students. A systematic search of seven databases was conducted to identify literature published in the United States between 2011 and 2024. Results: Twenty articles were analyzed and synthesized, then organized using Jeffrey's nursing universal retention and success model. Most of the literature reviewed focused on environmental and professional integration factors, with less of the literature addressing student affective factors. Conclusion: Although programs may differ, a framework that considers a variety of intrinsic and extrinsic factors is imperative in addressing issues specific to RN-to-BSN student retention. [J Nurs Educ. 2025;64(7):429–435.]